Spatial analysis along networks : statistical and computational methods - Okabe, Atsuyuki, 1945-; Sugihara, Kōkichi, 1948- (Hoboken, N.J. : Wiley, 2012)
In the real world, there are numerous and various events that occur on and alongside networks, including the occurrence of traffic accidents on highways, the location of stores alongside roads, the incidence of crime on streets and the contamination along rivers. In order to carry out analyses of those events, the researcher needs to be familiar with a range of specific techniques. Spatial Analysis Along Networks provides a practical guide to the necessary statistical techniques and their computational implementation.
Introduction -- Modeling spatial events on and alongside networks -- Basic computational methods for network spatial analysis -- Network Voronoi diagrams -- Network nearest-neighbor distance methods -- Network K function methods -- Network spatial autocorrelation -- Network point cluster analysis and clumping method -- Network point density estimation methods -- Network spatial interpolation -- Network Huff model -- GIS-based tools for spatial analysis along networks and their application.
Includes bibliographical references and index.
Keywords: Spatial analysis (Statistics); Spatial analysis (Statistics) -- Data processing; Geography -- Network analysis; MATHEMATICS -- Probability & Statistics -- General; Geography -- Network analysis; Spatial analysis (Statistics); Spatial analysis (Statistics) -- Data processing; Electronic books